Cross-Cultural Analysis of Spiritual Bypass: A Comparison Between Spain and Honduras - Motiño, Alejandra; Saiz, Jesús; Sánchez-Iglesias, Iván; Salazar, María; Barsotti, Tiffany J.; Goldsby, Tamara L.; Chopra, Deepak; Mills, Paul J. (Frontiers in Psychology, 2021)
Religion and spirituality (R/S) serve as coping mechanisms for circumstances that threaten people´s psychological well-being. However, using R/S inappropriately to deal with difficulties and problems in daily life may include the practice of Spiritual Bypass (SB). SB refers to avoiding addressing emotional problems and trauma, rather than healing and learning from them. On the other hand, coping strategies may be determined by the cultural context. This study aims to describe the presence of SB in individuals who may have experienced stressful situations and to understand the influence of culture on SB by comparing SB in two culturally different groups. The sample consists of a total of 435 people, 262 of Honduran nationality and 173 of Spanish nationality. Both groups are approximately equivalent in age and gender. The degree of SB, stressful events, perception of social support and spiritual well-being are examined, respectively, through the Spiritual Bypass Scale, and specific items and subscales from the Social Readjustment Rating Scale, Multidimensional Scale of Perceived Social Support, and the Functional Assessment of Chronic Illness Therapy - Spiritual Wellbeing. The results showed a higher spiritual well-being and use of SB in the Honduran sample as compared to the Spanish sample, but similar social support and stressful events. Furthermore, some of the factors predicting SB were different between the two samples. While age and a greater number of R/S practices were important in both samples, for the Honduran sample the variables that best explained SB were being a Christian, having greater social support, fewer stressful events, and greater attendance at church or temple. For the Spanish sample, however, the variable that best explained SB was studying R/S texts. Therefore, SB must be understood within the culture in which it develops, since in different cultural contexts it appears to relate to differing factors. Thus, SB becomes a possible functional or dysfunctional coping strategy depending on the social context.